Պատմության ինստիտուտ - Մելքոնյան, Աշոտ; Խաչատրյան, Կարեն (ՀՀ ԳԱԱ Պատմության ինստիտուտ)
During 70 years of the existence the Institute of History of NAS RA by means of its productive work realizes a special and important role in the study of the problems of the history of the Armenian people and the development of the Armenian historiography. Институт истории НАН РА за 70 лет существования своей плодотворной работой выполняет особую и важную роль в изучении проблем истории армянского народа, в развитии армянской историографии.
Keywords: Պատմություն; Ակադեմիաներ և գիտական հասարակություններ